Improving Teachers' Professional Competence through Technology Implementation for Education Quality Improvement in Mamasa District - Pawan, Fredy; Gasong, Dina; Tanduk, Rita (Universitas Muhammadiyah Makassar, 2024)
Teachers have a strategic role in improving the quality of education, especially in developing professional competencies that include mastery of material, learning strategies, and utilization of educational technology. This study aims to analyze the effect of educational technology implementation on improving teachers' professional competence in order to improve the quality of education in Mamasa district. This research uses a mixed methods approach, where qualitative methods are used to describe the implementation of educational technology in the learning process, while quantitative methods are used to analyze the relationship between teachers' professional competence and student achievement through data presented in the form of numbers and tables. The results show that teachers who implement educational technology in learning tend to have more effective teaching methods, increase student engagement and contribute to improved learning outcomes. However, there are still constraints in teachers' access to technology and digital literacy that need further attention. With continuous training and mentoring, the implementation of education technology can be a solution to improve teachers' professional competence and the overall quality of education in Mamasa district.